The Forgotten Massacre Budapest in 1944 - Pető, Andrea (De Gruyter, 2021)
The book discusses the history of a previously invisible massacre in Budapest in 1944 committed by a paramilitary group lead by a women. Based on court trials, interviews with survivors, perpetrators and investigators the book illustrates the complexities of gender memory. It discusses the events: massacre, deportation, robbery, homecoming, and fight for memorization from the point of view of the perpetrators and the family.